The end of mass homeownership? Changes in labour markets and housing tenure opportunities across Europe - Arundel, Rowan; Doling, John (Journal of Housing and the Built Environment, 2017)
With continued economic growth and expanding mortgage markets, until recently the pattern across advanced economies was of growing homeownership sectors. The Great Financial Crisis (GFC) has however, undercut this growth resulting in the contraction of homeownership access in many countries and the revival of private renting. This paper argues that these tenure changes are not solely a consequence of the GFC, and therefore, reversible once long-term growth returns. Rather, they are the consequences of more fundamental changes especially in labour markets. The very financialisation that fuelled the growth of homeownership has also led to a hollowing out of well-paid, secure jobs—exactly those that fit best with the taking of housing loans. We examine longer-term declines in labour market security across Europe from before the GFC, identifying an underlying correlation between deteriorated labour market conditions and homeownership access for young adults. While variations exist across European countries, there is evidence of common trends. We argue that the GFC both accelerated pre-existing labour insecurity dynamics and brought an end to offsetting such dynamics through the expansion of credit access with the likelihood of a return to an era of widespread homeownership growth starkly decreased.